Enhanced and Synthetic Vision 2008 2008
DOI: 10.1117/12.771992
|View full text |Cite
|
Sign up to set email alerts
|

Cybersickness and desktop simulations: field of view effects and user experience

Abstract: We used a desktop computer game environment to study the effect Field-of-View (FOV) on cybersickness. In particular, we examined the effect of differences between the internal FOV (iFOV, the FOV which the graphics generator is using to render its images) and the external FOV (eFOV, the FOV of the presented images as seen from the physical viewpoint of the observer). Somewhat counter-intuitively, we find that congruent iFOVs and eFOVs lead to a higher incidence of cybersickness. A possible explanation is that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Participants experienced all three types of VR and reported that the level of discomfort was lowest under the neutral condition. However, subsequent studies showed opposite results (Bos et al, 2010;Toet et al, 2008;Van Emmerik et al, 2011). That is, participants showed greater VR sickness when the FOV of the hardware and content were matched.…”
Section: Display Type and Modementioning
confidence: 98%
“…Participants experienced all three types of VR and reported that the level of discomfort was lowest under the neutral condition. However, subsequent studies showed opposite results (Bos et al, 2010;Toet et al, 2008;Van Emmerik et al, 2011). That is, participants showed greater VR sickness when the FOV of the hardware and content were matched.…”
Section: Display Type and Modementioning
confidence: 98%
“…Studies evaluating HMD VR sickness showed that it is a multifactorial problem and could be caused by any of the VR technical features related to the field of view, optical distortion, flicker, refresh rate, resolution, latency and poor tracking of visuo-motor feedback, slow update rate, etc. (Sharples et al, 2008;Toet et al, 2008;Jerald, 2016;Lu, 2016). The high compared to low realism graphics causes more visual flow and stronger sensory conflict, especially in case of mismatch between visual and vestibular ego-centric feedbacks, which leads to visually induced motion sickness (Toet et al, 2008;Keshavarz et al, 2015;Jerald, 2016;Lu, 2016;Yim et al, 2017;Ng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(Sharples et al, 2008 ; Toet et al, 2008 ; Jerald, 2016 ; Lu, 2016 ). The high compared to low realism graphics causes more visual flow and stronger sensory conflict, especially in case of mismatch between visual and vestibular ego-centric feedbacks, which leads to visually induced motion sickness (Toet et al, 2008 ; Keshavarz et al, 2015 ; Jerald, 2016 ; Lu, 2016 ; Yim et al, 2017 ; Ng et al, 2018 ). This could indirectly support our result that participants spent more navigation time in DT than HMD display as they experienced less VRISE and task effort in DT than HMD condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations